Ebola Virus Glycoprotein 1: Identification of Residues Important for Binding and Postbinding Events - Brindley, Melinda A. (American Society for Microbiology, 2007)
The filoviruses Ebola virus (EBOV) and Marburg virus (MARV) are responsible for devastating hemorrhagic fever outbreaks. No therapies are available against these viruses. An understanding of filoviral glycoprotein 1 (GP1) residues involved in entry events would facilitate the development of antivirals. Towards this end, we performed alanine scanning mutagenesis on selected residues in the amino terminus of GP1. Mutant GPs were evaluated for their incorporation onto feline immunodeficiency virus (FIV) particles, transduction efficiency, receptor binding, and ability to be cleaved by cathepsins L and B. FIV virions bearing 39 out of 63 mutant glycoproteins transduced cells efficiently, whereas virions bearing the other 24 had reduced levels of transduction. Virions pseudotyped with 23 of the poorly transducing GPs were characterized for their block in entry. Ten mutant GPs were very poorly incorporated onto viral particles. Nine additional mutant GPs (G87A/F88A, K114A/K115A, K140A, G143A, P146A/C147A, F153A/H154A, F159A, F160A, and Y162A) competed poorly with wild-type GP for binding to permissive cells. Four of these nine mutants (P146A/C147A, F153A/H154A, F159A, and F160A) were also inefficiently cleaved by cathepsins. An additional four mutant GPs (K84A, R134A, D150A, and E305/E306A) that were partially defective in transduction were found to compete effectively for receptor binding and were readily cleaved by cathepsins. This finding suggested that this latter group of mutants might be defective at a postbinding, cathepsin cleavage-independent step. In total, our study confirms the role of some GP1 residues in EBOV entry that had previously been recognized and identifies for the first time other residues that are important for productive entry.